2010
DOI: 10.1055/s-0030-1267849
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation Management

Abstract: To perform safe invasive procedures on patients on anticoagulation therapy, management of the patient's anticoagulation status is mandatory. For patients on anticoagulation therapy, a risk analysis of both the procedural risk of bleeding as well as the risk to the patient from discontinuing anticoagulation needs to be performed. For procedures at low risk of bleeding, the procedure may be performed with little change to the patient's anticoagulation regimen. For procedures with significant bleeding risk, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 8 publications
0
20
0
2
Order By: Relevance
“…Protamine was not available at the time of experimentation in this case. Due to the normally relatively short half-life of heparin (∼1.5 h) (41), and the non-linear heparin dose-response and elimination curves, protamine treatment is not always required (42), though may have been helpful in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Protamine was not available at the time of experimentation in this case. Due to the normally relatively short half-life of heparin (∼1.5 h) (41), and the non-linear heparin dose-response and elimination curves, protamine treatment is not always required (42), though may have been helpful in this case.…”
Section: Discussionmentioning
confidence: 99%
“…U RELY studiji koja je ispitivala efekte dabigatrana kod AF bolesnika pokazano je da dodavanje jednog ili dva antitrombocitna leka povećava rizik od krvarenja za 60 ili 130 %. Prednosti koje imaju NOAC u odnosu na VKA verovatno se održavaju i u dvojnoj i trojnoj terapiji, ali ova hipoteza do danas nije potvrđena u kliničkim studijama 14 . Tabela 1.…”
Section: Ponovno Uvođenje Antikoagulantne Terapije Posle Uspešne Pciunclassified
“…Važno je napomenuti da je potrebna potpuna individualizacija antitrombocitne i antikoagulantne terapije kod AF bolesnika koji su imali akutni koronarni sindrom (AKS) na osnovu aterotrombotskog, trombooembolijskog rizika i rizika od krvarenja. Oni se određuju na osnovu postojećih GRACE, CHA2DS2-VASc i HAS-BLED skorova 14 .…”
unclassified
“…Interestingly, it has been demonstrated that selective desulfation of heparin can significantly reduce its anticoagulant activity . Heparin also clears from the bloodstream rapidly, necessitating an increased frequency of administration . Therefore, a heparin formulation that features non‐/low‐anticoagulation and long‐acting properties is desirable and provides for a promising anti‐metastasis agent.…”
Section: Introductionmentioning
confidence: 99%